Drying creep in cyclic humidity conditions. (October 2015) - Cagnon, H.; Vidal, T.; Sellier, A.; Bourbon, X.; Camps, G.
Abstract: The paper deals with the dimensional variations of High Performance Concretes subjected simultaneously to cyclic water exchanges and loading. The aim is to quantify the drying creep amplitude in the case of variable humidity comparatively to a constant humidity. The tests are performed between 98% RH and 50% RH. Comparison between samples subjected to constant and cyclic humidity shows that, under loading, the deformations induced by hydric cycles are reversible whatever the drying history before loading. Moreover, the wetting cycles lead to progressive erasing of pre-loading drying effects. Specimens subjected to wetting cycles after loading present the same final drying creep as specimens that were not dried before loading, while specimens dried before loading and not subjected to a wetting cycle present less final drying creep. Therefore, results confirm that drying creep amplitude is reduced if concrete is partially dried before loading, but this reduction disappears if concrete is rewetted.